Gender issue :segregation, discrimination and inequality at work place in Sarawak civil service a case study of Padawan Municipil Council, Kuching. - Nyambong, Chumang (Universiti Malaysia Sarawak (UNIMAS), 2002)
The under representation of women in the higher and middle echelons of government service is an area of concern, insofar as these positions are critical in terms of gender sensitive policy making, program and project design as well as omplementation. Therefore, the aim of the study is to determine the institutional and personal obstacles that women face in their career development.